Falsafah Nenemo dan Kontribusinya Bagi Masyarakat Lampung - Bangsawan, Rozali (Universitas Islam Negeri Raden Intan Lampung, 2020)
The problems of human life today include culture. Cultural heritage that should be preserved and used as a reference in life, on the other hand is ignored and more attracted to foreign cultures, so that the culture of melting is eliminated. One of the noble cultural collections in Lampung society is nenemo. This research aims to find out how Nenemo philosophy and its contribution to the people of Lampung ?. This research belongs to the field research (field research) data obtained from interviews, observations and documentation, to analyze researchers' data using descriptive, interpretation and systematic methods. The results showed that the word Nenemo means: Nemen (working hard), Nedes (tenacious, resilient and patient), Nerimo (willingly accepting the provisions of God). Thus, the values contained in Nenemo's philosophy have a significant contribution to the people of Lampung. By preserving and instilling the values of Nenemo's philosophy in carrying out daily life, it will form a society that is hard working, does not like to depend on others and is always patient, and has a spirit of high sincerity in living life.